(untitled) (Biological Sciences - PJSIR, 2023)
Physiological parameters are good indicators for the development of water stress tolerant wheat genotypes through conventional plant breeding without involving of physiological traits it is hard task to developed the water stress tolerant thus present study is aimed to determine the general and specific combiners for yield and physiochemical trait. The mean square form analysis of variances showed that genotypes, treatment and treatment x genotypes were significant for all the traits like grain yield Kg/ha, biological yield Kg/ha, relative water content, leaf area, chlorophyll content, spike fertility and cell membrane stability. Among the genotypes TJ-83, NIA-Saarang, Sindhu, Benazir and TD-1 were proved good combiners for all the traits whereas F1 hybrids Benazir x NIA-Saarang, Benazir x Imdad-05, Sindhu x NIA-Amber and TJ-83 x Imdad-05 were showed good specific combiners for all the traits under water stress conditions. Above parent and hybrids should be utilized in breeding programme for the development water stress tolerant wheat genotypes.